Harmonizing Civil Litigation with Syariah Litigation in Islamic Banking: Malaysian Experience - Ayub, Zainal Amin; Hussain, Mohammad Azam; Hj. Ahmad Shariff, Nurretina; Ali, Hassan (The Malaysian Current Law Journal, 2007)
Islamic banking in Malaysia is very well established and accepted by consumers both Muslim and non-Muslim. Nevertheless matters concerning Islamic banking jurisprudence come under the ambit of the civil courts in Malaysia and not under the Syariah court system. This was established in the case of Bank Islam Malaysia Berhad v. Adnan Omar [1993] 3 CLJ 735. This article is based on a study which sought to examine the views of Syariah lawyers, Syariah court judges as well as members of the Advisory Board of Islamic Banks in Malaysia as to whether civil litigation is in harmony with Syariah in Islamic banking in Malaysia. The study also examines the views of the eminent minds as to some of the structural problem within the Syariah system in Malaysia concerning the adoption of Syariah in Islamic banking litigation